Design Criteria For Visual Presentation Produced By Non-Design Lecturers - Mat Sin, Nazirah (2008)
The study was aimed at identifying the most appropriate design criteria for lecturers with non-design background when producing visual presentation, and to produce a visual presentation template which meets the design criteria.